Decreasing expression of glucose‐regulated protein GRP78/BiP as a significant prognostic predictor in patients with advanced laryngeal squamous cell carcinoma. Issue 10 (17th June 2016) - Kaira, Kyoichi; Toyoda, Minoru; Shimizu, Akira; Imai, Hisao; Sakakura, Koichi; Nikkuni, Osamu; Suzuki, Masami; Iijima, Misa; Asao, Takayuki; Chikamatsu, Kazuaki
Abstract: Background: The immunoglobulin heavy chain binding protein (BiP)/glucose‐regulated protein 78 (GRP78) is important in the endoplasmic reticulum stress, and is highly expressed in various human cancers. The clinical and pathological features of GRP78/BiP are unclear in patients with advanced laryngeal squamous cell carcinoma (SCC). The purpose of this study was to investigate the clinicopathological significance of GRP78/BiP as a prognostic marker for laryngeal SCC. Methods: A total of 59 patients with advanced laryngeal SCC (stage III/IV) were analyzed, and tumor specimens were stained by immunohistochemistry for GRP78/BiP and Ki‐67. Microvessel density was determined by immunohistochemical staining for CD34 and p53. Results: Expression of GRP78/BiP was confirmed in 87% of cases. Decreased expression of GRP78/BiP was highly associated with positive expression of p53. Decreased GRP78/BiP expression was identified on multivariate analysis as an independent factor of decreased progression‐free survival (PFS). Conclusion: GRP78/BiP was found to be commonly expressed in laryngeal SCC, whereas its downregulation was found to serve a significant prognostic role for predicting poor survival in patients with laryngeal SCC with advanced disease. GRP78/BiP may be a potentially attractive target for the treatment of various human neoplasms. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1544, 2016